LITERATURE REVIEW FACTORS AFFECTING SERVICE PERFORMANCE: TRANSFORMATIONAL LEADERSHIP, TRUST ORGANIZATION AND ORGANIZATIONAL COMMITMENT - Munawar, N. Ahmad; Wulandari, Arviana; Djalaludin, Asep (Dinasti International Journal of Economics, Finance & Accounting, 2020)
The development of information technology has an impact on the paradigm of global economic, organizational and geopolitical development. The speed in making the right decisions in an organization will determine the direction of business and business development of a company in response to intense competition, both nationally and globally. Effectiveness and efficiency in determining human resources are the main strategic factors in winning future business competition. Good human resource management is an absolute requirement in managing an organization that will affect the company's service performance. This paper is a review of the strategic relationship between Transformational Leadership, Trust Organization and Organizational Commitment on the performance of company services. This research was conducted by looking at the three factors that are considered to have an effect on service performance, namely the Transformational Leadership, Trust Organization and Organizational Commitment factors through various relevant research methods and can explain in detail the relationship between service performance factors and Transformational Leadership, Trust Organization and Organizational Commitment.